Secured data center model based on cloud computing technology - Коваль, Оксана Сергіївна; Бондаровець, Сергій Сергійович; Гнатюк, Сергій Олександрович (Ukrainian Information Security Research Journal, 2016)
The rapid growth of information creates an urgent need for the establishment of large-scale storage and accumulation of data. The task of information collecting and storing is successfully resolved by data centers – tools that are able to secure and automate any business activity. Currently, almost all the service providers use a very promising technology for data centers – Cloud Computing, which has several advantages over traditional data centers. The problem of data protection that is trusted to the vendor, is so great that usually the risk of losing data in the «cloud» forever. In this paper, there is an analysis of existing models of data center technology based on Cloud Computing, which helped to identify the problem of information security. Therefore, in the paper there is proposed the model of secure data center based on technology of Cloud Computing, showed its theoretical foundation and conducted appropriate simulation, the result of which is the fact that the developed model solves the problem of information security in the data center and can be used in creation data centers based on technology Cloud Computing in different spheres.